Saving the World, One Server at a Time, Together. - Ranganathan, Parthasarathy; Jichuan Chang (Computer (00189162), 2011)
Achieving the next order-of-magnitude improvement in power management requires a holistic approach to how we study and reason about energy efficiency and how we optimize system design across traditional implementation boundaries.